Acoustic flow meter performance assurance outside the limits of measurement - Mikhail V. Lapin; Andrey O. Grinin; Kirill V. Shkarin; Kambiz Soury (RUDN Journal of Engineering Research, 2019)
Article is dedicated to liquid flow measuring by acoustic flow meters. Manufacturers establish the allowable measurement range (nominal), within which the measurement error is minimal, that’s why their measuring span is limited, and the measurement error when operating in off-design modes is unacceptable. The basic task of this research is to expand the range of flow measurements of acoustic liquid meters. V.A. Fafurin and M.K. Galeev in their work “Calculation of the correction coefficient of the ultrasonic flow meter” have already considered the problem of measuring the flow rate of acoustic devices. In their study was presented a method for calculating the correction coefficient, which depended on the flow regime in the pipe. But this technology is applicable for change-less flow regime pipes. In this article, the authors propose to use a coefficient that has a functional dependence on the magnitude of the flow, obtained empirically. The article describes the stages of the study: the method of calibration of the device, methods of analysis and processing of verification data by PC, the algorithm of measurement system implementation in power engineering equipment, system performance check. The system presented in the article allows to expand the range. The proposed model will be useful for enterprises.